Word reading, vocabulary, and mental health problems in adolescent girls and boys with intellectual and developmental disabilities. (4th March 2021) - Eldblom, Julia; Boström, Petra; Broberg, Malin; Åsberg Johnels, Jakob
Abstract : Reading difficulties are linked to several disadvantages in the general population. Less is known about correlates of reading difficulties in individuals with intellectual and severe developmental disabilities (IDD). Vocabulary and word reading were assessed in 112 adolescents with IDD, recruited from Special needs comprehensive schools in Sweden ( grundsärskolor in Swedish). Proxy-ratings of mental health were collected from teachers and parents for a subset of the participants. Relationships between all measures were investigated. Reading and vocabulary were poorly developed in both groups and significantly associated. While mental health problems were common, there were no significant associations with word reading or with vocabulary knowledge. Thus, the study did not confirm an association between reading difficulties and mental health problems in adolescents with IDD. Still, the frequency of mental health problems and the low reading abilities point to the need for further intervention for adolescents with IDD.